Design and implementation of a new module to evaluate the cost of air pollutant abatement measures. (1st September 2022) - Bessagnet, Bertrand; Pisoni, Enrico; Thunis, Philippe; Mascherpa, Alessandro
Abstract: Integrated Assessment Model provides a useful framework for evaluating different aspects of air quality policies, spanning from abatement measures to emissions, concentrations, health impacts and costs. These models are then useful to provide a holistic view of the impacts of policies, so that ex-ante one can evaluate how various policies will impact air concentrations, health benefits and implementation costs. Among these Integrated Assessment Models, SHERPA (Screening for High Emission Potentials on Air) has been recently used to evaluate the impact of policies, covering all aspects from measures to health, but without being able to provide the dimension related to abatement measures costs. In this paper we fill this gap, developing a module able to associate to a SHERPA scenario its related implementation costs. This paper describes how this module has been developed and provide a concrete application of this tool. Results of this module can be useful to provide a full cost-benefit analysis of alternative policies based on technological changes, covering both internal costs (costs of abatement measures) and external costs (related to human health impacts of air quality). Highlights: A new module on cost calculation is implemented in SHERPA. A first step consists in digesting the GAINS data to produce an actionable statistic cost database. A second step explores this database within SHERPA to determine the costs. An example of application is provided.